As olimpíadas brasileiras de matemática das escolas públicas na formação de professores e alunos - VIANA, Cléber Soares Viana (Universidade Federal do Pará, 2020)
The related article has as objective to embroider the OBMEPS (Olimpíadas Brazilian of Mathematics of the Public Schools); we will also speak of the historical origin of the Olimpíadas of the Mathematics, and as boarding final we will comment of that it forms the OBMEPS has contributed for a formation of pupils and professors in the Public Schools of the regions Northeast (Ceará), Southeast (Mine-Generality) and North, specifically in the Cities of Barcarena and Parauapebas.